Simulated maternal pre‐spawning stress affects offspring's attributes in farmed Atlantic salmon Salmo salar (Linnaeus, 1758). (21st October 2013) - Eriksen, Marit Skog; Poppe, Trygve T; McCormick, Mark; Damsgård, Børge; Salte, Ragnar; Braastad, Bjarne O; Bakken, Morten
Summary: In fish hormones are released into the nutritive yolk sac during oogenesis in quantities that mirror female plasma levels, thus implying a potential for the maternal endocrine state at spawning to affect offspring characteristics. In the present study, mature female Atlantic salmon, Salmo salar, were given intraperitoneal cortisol implants to investigate potential impacts of simulated stress on offspring ontogeny. Maternal cortisol levels reduced fertilization success and affected several offspring characters: lowered initial survival rates, impaired growth early in life and increased prevalence of morphological abnormalities in adult individuals. In addition, offspring from cortisol administered females displayed increased locomotor activity in an acute confinement test. These results suggest that developmental trajectories of salmon offspring can be considerably altered if their mothers experience severe stress during the final stages of gametogenesis. The present findings may have conceptual and applied ramifications as they demonstrate a mechanism that links the maternal environment to subsequent viability of the progeny.